KAJIAN DESAIN ALUN-ALUN KOTA MALANG BERDASARKAN PERSEPSI DAN PREFERENSI PENGUNJUNG - Rizki Alfian; Hesti Triana Soelistyari; Delviany Lisonio Taty (BUANA SAINS, 2020)
A city will develop physically and socio-culture. The Center of the city is a public space, which is the center for all activities of the urban community, whether they are political, social, or economic. Alun-Alun of Malang city consists of locations that are unique to one another. The conditions created in the Alun-Alun generate perceptions and preferences for visitors in assessing aspects to give an opinion regarding the design of the Alun-Alun of Malang city. This study aims to explain people's perceptions and preferences of Alun-Alun of Malang city, describes the design of the Square based on perceptions and preferences. This research was conducted in Alun-Alun of Malang city at Merdeka Selatan, Kauman, Klojen District. The method used in this research is the quantitative descriptive analysis method. Processing and analysis of respondent questionnaire data using Chi-Square analysis test. Based on the results of the study, it can be concluded that there is a significant influence between gender on the perceptions and preferences of visitors to aesthetic beauty and recreation areas, elements of flowering plants, pool elements, and round plant crown shapes. Recommendations for the management Alun-Alun of Malang city in terms of the value of the equation are 75% of respondents want Alun-Alun of Malang city to be arranged regularly or with various types of plants, 73.33% of respondents want a square with a garden that has flowering plants/trees and 61.67% as a place of recreation.A city will develop physically and socio-culture. The Center of the city as a public space, which is the center for all activities of the urban community, whether they are political, social or economic. Alun-alun of Malang city consists of locations that are unique to one another. The conditions created in the Alun-alun generate perceptions and preferences for visitors in assessing aspects to give an opinion regarding the design of the Alun-alun of Malang city. This study aims to explain people's perceptions and preferences of Alun-alun of Malang city, describes the design of the Square based on perceptions and preferences. This research was conducted in Alun-alun of Malang city at Merdeka Selatan, Kauman, Klojen District. The method used in this research is quantitative descriptive analysis method. Processing and analysis of respondent questionnaire data using Chi-Square analysis test. Based on the results of the study, it can be concluded that there is a significant influence between gender on the perceptions and preferences of visitors to aesthetic beauty and recreation areas, elements of flowering plants, pool elements, and round plant crown shapes. Recommendations for the management Alun-alun of Malang city in terms of the value of the equation are 75% of respondents want Alun-alun of Malang city to be arranged regularly or with various types of plants, 73.33% of respondents want a square with a garden that has flowering plants / trees and 61.67% as a place of recreation.